Adolescents' perception of the healthiness of snacks. (June 2016) - Bucher, Tamara; Collins, Clare; Diem, Sabine; Siegrist, Michael
Highlights: A product-sorting task was used to assess adolescents' perception of the healthiness of snack foods. Sugar, fat, fruit and nut content significantly impact adolescents' perception of snacks' healthiness. Adolescents' perceptions accord well with validated nutrient profile scores. Abstract: Changes in snacking habits in developed countries are a growing cause for concern, since foods and beverages commonly consumed as snacks, tend to be both energy dense and nutrient poor. Adolescents are characterised by frequent snack consumption. Therefore, promoting more healthful snack choices to adolescents is important for optimising nutrient intake and lowering the risk of chronic disease. The ability to evaluate the healthiness of snacks is essential to making healthy choices. Previous research has shown that health claims can influence consumers' perceptions of food products. However, little is yet known about consumers' perceptions of how nutritious or healthy specific foods or beverages are. This knowledge is important for planning successful interventions and designing healthy snacks that will also appeal to population groups with a higher dietary risk, including adolescents. The aim was to investigate how adolescents evaluate the healthiness of snacks currently available for consumption in school environments. Seventy-five adolescents participated in a sorting task and evaluated the healthiness of 37 representative snacks. The data were analysed using hierarchical multiple regression and cluster analysis. The sugar ( β = −.51, P < .001), fruit ( β = .49, P < .001), total fat ( β = −.41, P = .002) and nut content ( β = .35, P = .002) were significant predictors of snacks' perceived healthiness. The findings of this study are important for tailoring future interventions to promote healthy eating and setting priorities for nutrition education.